(untitled) (Bangladesh Pharmaceutical Journal, 2021)
The study aimed to develop and evaluate an immediate-release tablet dosage form of Linagliptin. Different concentrations (ranges 5-10%) of super-disintegrants, Croscarmellose sodium (CCS), and Sodium starch glycolate (SSG) were used to prepare nine tablet dosage forms (F1 to F9) through the direct compression method. The compatibility of the formulations was evaluated by FTIR to reveal any possible drug-excipient interactions and it was proved to be compatible with all formulations. Precompression (bulk density, tapped density, Carr’s index, Hausner’s ratio, and angle of repose) and post-compression parameters (weight variation, hardness, thickness, and friability) were analyzed for all tablets and the results were found satisfactory as well as within limits as per USP guidelines. All the formulated batches (F1 to F9) exhibited disintegration of tablets within 2 minutes, where formulation F9 represented the lowest disintegration time (51±3 sec) which was also found significantly better than the marketed product (310±5 sec). In terms of drug dissolution, 90% of drug release was observed for all nine formulations within 45 minutes and formulation F9 (5% CCS and 5% SSG) illustrated the rapid and highest dissolution rate compared to the marketed one’s, 100% drug release at 20 minutes and 91.77 % drug release at 30 minutes successively. The respective data sets of drug release were mathematically fitted to several kinetic models and for all formulations, drug release pattern obeyed first-order kinetics amongst those, formulation F2 (r2= 0.98), F4 (r2= 0.99), F5 (r2= 0.98), and F9 (r2= 0.97) were found to be best fitted in this kinetic norm. Based on disintegration time and dissolution data comparison to a brand leader market product, F9 was experienced as the best formulation. Furthermore, it was observed that if SSG and CCS were combined, then these two parameters were more improved compared to their separate uses. Thus, incorporation of the optimum amount of super-disintegrants in a formulation showed rapid swelling, faster disintegration as well as ease of dissolution of tablet dosage forms. Bangladesh Pharmaceutical Journal 24(2): 168-179, 2021